Presentación. Revista Kawsaypacha: Sociedad y Medio Ambiente; Núm. 15 (2025) - Castro, Augusto (Pontificia Universidad Católica del Perú, 2025)
We present issue number 15 of our journal Kawsaypacha: Society and Environment. This edition continues our ongoing effort to compile research related to the social and environmental challenges of our time. The issue is divided into two sections. The first section features the Dossier: Environmental Policy and Management, which has been organized and prepared by Dr. Iván Ortiz. It includes twelve articles dedicated to topics such as environmental policy, environmental control and management, and studies on the environment. The second section, Academic Articles and Essays, contains several additional contributions addressing diverse topics such as watershed management, tourism policies, issues related to the co-production of knowledge, and proposals aimed at improving the planet’s conditions.

Tenemos el placer de presentar el número 15 de nuestra Revista Kawsaypacha: Sociedad y Medio Ambiente. Esta edición continúa con el esfuerzo de recoger investigaciones ligadas a los problemas sociales y ambientales de nuestro tiempo. El número tiene dos secciones. La primera sección presenta el Dossier: Política y Gestión Ambiental que ha sido organizado y preparado por el doctor Iván Ortiz; cuenta con doce artículos dedicados a las temáticas de política ambiental, control y gestión ambiental, y estudios sobre el medioambiente. En la segunda sección: Artículos y Ensayos Académicos se publican varios artículos más que recogen otras temáticas como el manejo de cuencas, políticas de turismo, cuestiones relativas a la coproducción del conocimiento y propuestas para mejorar las condiciones del planeta.
Presentation N° 15 (2025)
Keywords: Presentación; https://purl.org/pe-repo/ocde/ford#2.07.01